Greenwashing as Environmental Fraud: Highlighting the Lack of Regulation and Law Enforcement in Indonesia - Lebie, Romansyah Fitra; Br. Sihombing, Rio Riccha (Universitas Negeri Gorontalo, 2025)
Greenwashing is a practice that is increasingly prevalent in Indonesia, along with increasing consumer awareness of environmental sustainability. This phenomenon occurs when companies claim that their products are environmentally friendly, but the claims are not supported by legitimate evidence or are merely a marketing strategy. This article aims to explore the greenwashing phenomenon in Indonesia, identify its impact on consumers and the environment, and analyze the lack of regulation and law enforcement governing sustainability claims. Based on descriptive qualitative research, it was found that greenwashing harms consumers financially and undermines their trust in legitimate sustainability claims. In addition, greenwashing also hinders progress in environmental protection efforts by diverting attention from more effective solutions and reducing the competitiveness of truly green products. The lack of clear regulations and adequate oversight by relevant agencies in Indonesia exacerbates this problem. Therefore, strengthening more specific regulations and stricter law enforcement are urgently needed to create a more transparent market and support true sustainability. This article recommends improved regulations, increased capacity of oversight agencies, and more severe sanctions to address greenwashing practices and support broader environmental protection